Hydrogen sulfide-releasing therapeutics - how far have we come in clinical studies? - Marinko, Marija; Novaković, Aleksandra (Archives of Pharmacy, 2023)
Hydrogen sulfide (H2S) is the youngest member of the gasotransmitters family consisting of nitric oxide (NO) and carbon monoxide (CO). This signalling molecule is implicated in the regulation of a wide range of processes, such as inflammation, pain, and tissue repair, and has an important role in signalling processes affecting cardiovascular health, either as an independent effector or as an enhancer of the NO system. With the discovery of the H2S role in the pathogenesis of many diseases, the development of new pharmaceuticals that could be useful in conditions with disturbed levels of endogenous H2S began. Today, the development of H2S-releasing drugs has reached the level of clinical studies. Drugs such as SG1002, aimed at the treatment of heart failure, and ATB-346, aimed at the treatment of arthritis, have been tested in Phase I/II clinical studies and have shown significant therapeutic potential. Additionally, it has been shown that some already known drugs, such as zofenopril, produce part of their beneficial effects by releasing H2S.Evidence from clinical studies presented in this paper encourages further clinical testing of H2S-based therapeutics and the possibility of their application in a wide range of diseases, such as hypertension, diabetes and chronic kidney disease.